Development of a project-based home materials model in science learning to enhance students' creative disposition - Nanang Rahman; Nursina Sari; Hafiza Abas (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This study develops and evaluates the feasibility of a Project-Based Home Materials (PjBL-HM) model in science learning to enhance students' creative disposition at the elementary level. Creative disposition—comprising inquisitiveness, persistence, imagination, collaboration, and discipline—is a crucial 21st-century competence. However, conventional science instruction often lacks contextualization, active engagement, and opportunities for creative thinking. The PjBL-HM model integrates household materials into science projects, providing a low-cost and locally relevant alternative for schools with limited laboratory infrastructure. Employing the Educational Design Research (EDR) method, the model was validated by experts and tested with 28 fifth-grade students for practicality, and with two groups (VA and VB, 28 students each) for effectiveness. Data were collected through expert validation sheets, observation checklists, student questionnaires, and pre-/post-tests using a creative disposition scale. Results showed that the model had high levels of content and construct validity (average scores of 3.87 and 3.85, respectively). The practicality test yielded an average score of 4.27, indicating strong student engagement and ease of implementation. The effectiveness analysis based on N-gain scores implied that the experimental group (VA) achieved a higher mean N-gain (0.76) than the control group (VB) (0.45), indicating a substantially greater improvement in students’ creative disposition. These findings indicate that the PjBL-HM model is valid, practical, and effective in fostering creative dispositions through contextualized, project-based science learning using everyday materials.